Curds in the way: A milk curd obstruction review and normal sonographic bowel appearances using a novel scoring system in neonates on fortified breast milk feeds - Kimble, Lara L; Perry, David; Bach, Katinka P (Journal of medical imaging and radiation oncology, 2024)
Introduction Fortified expressed breast milk (FEBM) is a standard of care for premature and low birth weight neonates, but comes with an elevated risk of a rare but re‐emergent pathology called milk curd obstruction (MCO). Little is known about normal sonographic appearances of bowel contents in this feeding setting, making the recognition of abnormalities difficult. Thus, we aimed to describe appearances that may be considered typical pre‐ and post‐fortifier inclusion. Methods Ten neonates of <32 weeks' gestation or a birth weight of <1,800 g recruited from Auckland City Hospital Neonatal Intensive Care between 1/5/2019 and 10/9/2019 received bowel ultrasounds within 24 h before and 10–14 days after starting FEBM. Bowel contents in six abdominal regions were assigned scores of 1–6 based on increasing solidification. Results Lower gestational age was correlated with more solid contents on the pre‐fortifier ultrasound (P = 0.02). Fortifier was significantly associated with increasing solidity, particularly in the left abdomen (P < 0.001). The left lower quadrant and rectum accounted for much of this change (P = 0.012 and P = 0.002). One subject who subsequently developed a clinical picture consistent with early MCO had uniquely demonstrated non‐rectal solid contents (score 6). The interobserver kappa score for two assessors was 0.91 (95% CI 0.94–0.99) on still images. Conclusion This small cohort demonstrated increasing bowel content solidification after breast milk fortification using a novel ultrasound scoring system with good interobserver agreement. Non‐rectal solid contents (score 6) appeared atypical. Ultrasound shows promise for its non‐irradiating diagnostic utility in the setting of early milk curd disease evaluation of the premature neonate.